Innocent Fun or 'Microslavery'? - Harvey, Hayden; Havard, Molly; Magnus, David; Cho, Mildred K.; Riedel‐Kruse, Ingmar H. (Hastings Center Report, 2014)
In 2011, Ingmar Riedel-Kruse's bioengineering laboratory at Stanford University publicized an application that uses paramecia for what the researchers termed 'biotic games.' These games make use of living organisms, computer programs, and lab equipment to implement games like Pong, Pac-man, and soccer. Gamesand related activities are often considered nonserious or trivial, whereas life, biological systems, and science are treated very seriously in moral analysis and public perception. The manipulation of living matter frequently engenders at least some controversy in the marketplace of ideas, and using living things in games is no exception. Some of the objections lodged against biotic games have appeared in the ethics literature on similar topics; however, the addition of an entertainment element introduces some objections distinct from those about similar cases, as the online comments vividly illustrate. We aim to explore and address the objections in this paper, using the comments to organize and launch the discussion. In scientific work, there is typically a presumption of some prospect of translation and application of generated knowledge for public benefit. In the case of biotic games, these applications are not self-evident. Because of this, a serious analysis of the justifications, limitations, and features of biotic games is warranted. To this end, we outline key ethical limits that ought to be placed on these activities as well as the obligations that these activities generate for researchers, other professionals, and lay people who design, implement, use, and play them.